Modelling Services for Interoperability Negotiation - Coutinho, C.; Cretan, A.; Jardim-Goncalves, R. (Proceedings of the 2nd International Conference on Model-Driven Engineering and Software Development (MODELSWARD 2014), 2014)
The evolution of businesses, driven by the advent of the internet and subsequent globalisation, was very quick and sudden. Enterprises that had traditional development strategies and that were used to slow changes are suddenly feeling the urge to evolve or face obsolescence. This fast-paced evolution frequently leads to mistakes and erroneous decisions, many of which are solely detected after a long period. When this happens, frequently the only solution is to return to a previous stable business stage before proceeding. The EU co-funded FP7 TIMBUS project comprises tools and techniques to improve business continuity featuring an intelligent strategy for digital preservation of business assets and environments based on risk- management. This paper proposes the modelling of service-based negotiation strategies to help in two phases: First in the definition of the enterprise business interoperability strategy, and second, in the reasoning of assets and concepts needed for the capture of digital preservation of business assets.